2000
DOI: 10.1063/1.373342
|View full text |Cite
|
Sign up to set email alerts
|

Linear variable differential transformer sensor using Fe-rich amorphous wires as an active core

Abstract: Results concerning linear variable differential transformer (LVDT) displacement measurements using Fe77.5Si7.5B15 amorphous wires as movable core are presented. Taking advantage of the large Barkhausen (LBE) effect in amorphous wire, a small exciting field and a small number of windings in the secondary coils are necessary to get an large output signal of the LVDT. The thermal noise of the output becomes low, due to the small number of coil turns, increasing thus the sensitivity of the LVDT. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As a result, Drumea and Vasile suggested the use of an MSP430F149 chip as a signal adjuster for LVDT to improve on this problem; this chip also has additional functions, such as providing serial communication and malfunction testing. Saxena and Lal seksena (2000) presented a type-dependent compensatory LVDT. Experimental results showed that changes produced in the production of highly-sensitive and higher linear changes while being subject to external environmental impacts are not excessive; the system actually provides temperature compensation to maintain relatively good data transmission quality even in poor environments.…”
Section: Literature Surveymentioning
confidence: 98%
“…As a result, Drumea and Vasile suggested the use of an MSP430F149 chip as a signal adjuster for LVDT to improve on this problem; this chip also has additional functions, such as providing serial communication and malfunction testing. Saxena and Lal seksena (2000) presented a type-dependent compensatory LVDT. Experimental results showed that changes produced in the production of highly-sensitive and higher linear changes while being subject to external environmental impacts are not excessive; the system actually provides temperature compensation to maintain relatively good data transmission quality even in poor environments.…”
Section: Literature Surveymentioning
confidence: 98%
“…The standard material for the LVDT sensor core is ferrite; FeNi materials are used at low temperatures at which ferrites fail [65]. Very small LVDT sensors were designed with cores made of amorphous wire [66,67]. The basic ratiometric temperature compensation provides 0.15% error in a wide temperature range [59], with a temperature coefficient below 100 ppm K −1 .…”
Section: Linear Transformer and Inductance Sensorsmentioning
confidence: 99%
“…Apart from these, the rather classical inductive effects [93] have been implemented in the form of the fluxgate set-up [94] for accurate field detection and the linear variable differential transformer (LVDT) for displacement sensing [95]. As well as these magnetic effects, related electromagnetic effects such as the Hall effect, the quantum Hall effect and the SQUID are able to detect field.…”
Section: Domain Rotation Dynamics Domain Rotation Dynamics Hasmentioning
confidence: 99%